2022
DOI: 10.1007/s43440-022-00434-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS CoV-2 /COVID-19 infection on the course of advanced chronic liver disease and hepatocellular carcinoma

Abstract: Background About 20% of patients infected with SARS-CoV-2 develop COVID-19—the disease that has dominated health care in the last two years. The course of COVID-19 in patients with advanced liver disease tends to be severe, patients also suffer from a higher risk of complications and death. The primary object of this study was to assess the risk and causes of death in patients with cirrhosis and hepatocellular carcinoma (HCC). Materials and methods From a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In fact, the immune system surveillance of these patients is depressed, also because of malnutrition and subsequent anemia, hypoproteinemia. Altogether, these factors can favor infection by SARS-CoV-2 [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the immune system surveillance of these patients is depressed, also because of malnutrition and subsequent anemia, hypoproteinemia. Altogether, these factors can favor infection by SARS-CoV-2 [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Molecularly, immunomodulators used for transplanted long-term maintenance are able to down-regulate the second phase of SARS virus infections. In fact, in this step, there is a significant CD4+ T cell count drop, and CD8+ T cell and macrophages reduced function with cytokine cascade and subsequent COVID-19 exacerbation [ 78 ]. Whenever this storm is inhibited by immunosuppressors, there is an elevated viral load with a prolonged disease that can cause increased disease severity in transplant recipients [ 11 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[51,52] It has been shown that there is a potential relationship between liver carcinoma and COVID-19, and this relationship may be related to the aberrant expression of hub genes Hmox1, TLR4, ALB, TTR, and RBP4. [53] In previous studies, Hmox1 has also been suggested as a novel target for the treatment of autoimmune diseases and it plays an important role in oxidative stress response. [54] In the study of pharmacological treatment of COVID-19, we know that chloroquine and Ridgavir have a good effect on the prevention of COVID-19, while hydroxychloroquine and azithromycin can also stop the replication of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…An international, multicenter, retrospective, cross-sectional study, including two hundred fifty patients from 38 centers, reported that 18.4% of patients with HCC died within the first 30 d from the onset of COVID-19 symptoms, and that the mortality rate in that period was 20.25% in patients with HCC history and 12.96% in those with de novo HCC[ 78 ]. COVID-19 in HCC patients tends to be more severe and leads to exacerbation of the liver disease[ 79 ]. HCC patients infected with COVID-19 are at a higher risk of complications, ICU admission, and death than the patients without cancer[ 80 ].…”
Section: Covid-19 In Patients With Pre-existing Liver Diseasementioning
confidence: 99%